Rapid Uptake of the Subcutaneous Injectable in Burkina Faso: Evidence From PMA2020 Cross-Sectional Surveys - Guiella, Georges (Glob Health Sci Pract, 2018)
The subcutaneous (SC) injectable, widely known by its commercial name Sayana Press, has potential to improve access to contraceptive methods. In Burkina Faso, SC-injectables were first piloted in select regions in 2014 and introduced nationally in 2016. PMA2020 is the first national survey to track programmatic progress of SC-injectable introduction at both population and health facility levels in the country across 2 rounds of data collection: March–May 2016 and November 2016–January 2017. Over this 6-month period, SC-injectable availability at public service delivery points increased from 50% to 85%, largely driven by increases in availability among the non-pilot regions. In terms of use, while the modern contraceptive prevalence rate among all women remained constant at about 23%, SC-injectable prevalence nearly doubled from 1.1% to 2.0%, making up approximately 9% of all modern method users in Burkina Faso by late 2016, though the difference was not statistically significant. Increases were comparable between pilot and non-pilot regions. While the difference was not statistically significant, more rural women were using the method compared with their urban counterparts in the pilot regions, an interesting finding considering the opposite pattern is generally true for contraceptive prevalence nationally. In summary, following national scale-up, data show substantially improved availability of SC-injectables at service delivery points and potential for changes in the method mix in Burkina Faso. In order to further improve contraceptive access and choice, scale-up of community-based distribution of SC-injectables should be considered, especially among rural populations with higher unmet need for family planning.